2019
DOI: 10.1007/s11764-019-0732-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a survivorship needs assessment planning tool for head and neck cancer survivor-caregiver dyads

Abstract: Purpose: The objectives of this study were to test the acceptability and feasibility of a survivorship needs assessment planning (SNAP) tool for head and neck cancer (HNC) survivors and caregivers, evaluate short-term changes in psychosocial outcomes after completing the SNAP session and develop strategies for system refinement. Methods:We used a prospective one-group design and mixed methods with HNC survivors and caregivers (N=25 dyads). Participants completed baseline and 6-week surveys before and after com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…One previous dyadic, web-based intervention developed in a qualitative study using interactive health communication technologies has shown a promising effect in facilitating the HNC survivors and caregivers during the usability testing period. 66 Sterba and colleagues 24 tested the acceptability and feasibility of a technology-based care planning tool (SNAP) and found it was productive to assess and address HNC dyads’ dynamic needs. In a wellness program interest survey, caregivers reported their preference to receive programs delivered by mail including tangible and mobile materials.…”
Section: Research Implicationsmentioning
confidence: 99%
“…One previous dyadic, web-based intervention developed in a qualitative study using interactive health communication technologies has shown a promising effect in facilitating the HNC survivors and caregivers during the usability testing period. 66 Sterba and colleagues 24 tested the acceptability and feasibility of a technology-based care planning tool (SNAP) and found it was productive to assess and address HNC dyads’ dynamic needs. In a wellness program interest survey, caregivers reported their preference to receive programs delivered by mail including tangible and mobile materials.…”
Section: Research Implicationsmentioning
confidence: 99%
“…Thirteen studies targeted surveillance and management of psychosocial effects (Table 2). Four studies focused on psychosocial outcomes of cancer treatment as the primary study outcome, including one RCT with a high risk of bias 21 and three non‐randomized studies with a medium 28 to high risk of bias 34,40 . The RCT studied sexual interest after a stepped care program intervention targeting psychological distress; this trial did not show a statistically significant effect 21 .…”
Section: Resultsmentioning
confidence: 99%
“…The RCT studied sexual interest after a stepped care program intervention targeting psychological distress; this trial did not show a statistically significant effect 21 . The non‐randomized studies looked at the effect of a nurse‐led intervention on psychosocial adjustment and health‐related quality of life (HRQOL) showing no statistically significant difference between groups, 28 the effect on self‐efficacy with a web‐based tool showing an improvement with descriptive statistics but no tests of significance, 34 and a statistically significant improvement in depression, unmet needs, and survivorship knowledge in both survivors and care‐givers 40 . Of note, this was the only study identified by this systematic review that targeted an intervention to the patient‐caregiver dyad rather than the survivor alone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations